Analysis of Drying Air Temperature on Moisture Content in Coffee Beans Using a Fluidized Bed Dryer with Perforated Plates - Nanang Ruhyat; Haris Ilman Fiqih; Hilmy Nurfuad (Universitas Dr Soetomo, 2022)
Fluidized Bed Dryer with perforated plate bed is used as drying for coffee processing. This study succeeded in reducing the water content of coffee beans by 0.11% within 30 minutes of drying more evenly with fluidization on coffee beans. The level of maturity of coffee beans can be achieved at a control set temperature of 200°C the coffee beans undergo a light roasting process with the center of the coffee beans receiving 83.8°C, at a temperature of 250°C the coffee beans undergo a medium roasting process with the center of the coffee beans receiving 130°C, and at the control set temperature of 300°C the coffee beans underwent a dark roasting process with the center of the coffee beans receiving a temperature of 107.6°C. The advantage of this Fluidized Bed Dryer with perforated plate bed compared to other mechanical dryers lies in its low energy requirements, which depend on the heater and blower power as its main components.